Credit and financial policy in Austria in XIX – at the beginning of XX centuries - Mikhail Sergeyevich Chernov (Наука. Инновации. Технологии)
The features and main stages of credit and financial policy of Austria in XIX – at the beginning of XX centuries and conditions of its transition to the gold standard are considered in the article